Flexible work arrangemnets availability and their relationship with work-family-conflict: the moderating effect of emplyment nature and job status - Rahman, Mohammad Mizanur; Abdul, Mohani; Ali, Noor Azman; Uddin, Mohammad Jamal; Rahaman, Mohammad Saidur (IJENS Publishers, 2019)
The present study has explored the moderating effects of employment nature and job status on the relation between Flexible Work Arrangements (FWAs) and Work-Family-Conflict (WFC). Cross-sectional survey research design has been used and a structured self-administered survey questionnaire used to collect data from 330 employees working on private and public organizations in Bangladesh. Different statistical measures such as descriptive statistics, zero order correlation, Ordinary Least Square (OLS) multiple regression analysis, interaction regression and F-test for model fit were used to explore research observations and statistical verification of findings. The findings of this research is FWA is negatively related with WFC {B= -0.408, t (2.311) =-5.07, p<.000} and also cause to reduce WFC (Î²= - 0.283). On the other hand, employment nature and job status have moderating effect on FWAs and WFC. The most consistent finding in this regard suggests that FWAs is a more powerful mechanism for private organization employees with greater job responsibilities than employees (with less responsibility at work) in government organizations.